Faktor-Faktor Yang Memengaruhi Cash Holding Pada Perusahaan Manufaktur - Agselia, Agustin Ekadjaja (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of research is to obtain empirical evidence about the impact of profitability, firm size, leverage, and capital expenditure towards cash holding. This study used 34 manufacture companieslisted on IDX im 2016-2018 selected using purposive sampling method. The data used are secondary data in the form of financial statements. Data analysis was performed with descriptive statistics and hypothesis testing with data panel regression analysis using Eviews version 10. The results of this research are firm size has no significant effect towards cash holding , meanwhile leverage and capital expenditure has negative and significant effect towards cash holding, and for profitability it has positive and significant effect towards cash holding. For further research, it is recommended to extending the period of the study, adding other independent variables, and use other proxy.